Implementasi Program Identitas Kependudukan Digital (IKD) Di Balai RW Kelurahan Kalirungkut Surabaya - Rania Riska Vindy Aprilia; Kalvin Edo Wahyudi (Peneliti.net, 2023)
The Digital Population Identity Program is one of the government's efforts to reduce the use of blank e-KTPs which will be discontinued in early 2024, by the Ministry of Home Affairs. This program is carried out in RW halls to make it easier for the community to carry out this program. It is hoped that with the IKD service at the RW hall, the Surabaya Population and Civil Registry Office's target regarding the IKD service program can be achieved. This study aims to describe the implementation program of Digital Population Identity in the RW hall of the Kalirungkut Village. This study uses qualitative methods using primary and secondary data sources and data collection techniques used are observation and interviews using indicators of measurement of implementation policy theory from George C. Edwards III theory. The results of this study state that the factors that influence success in realizing the implementation of policies in the IKD program at the Kalirungkut Village Hall are good and have clear directions. The communication is good, the attitudes or attitudes that are accepted by the community are also good, then the resources in implementing the IKD service program are also very good.